GridUI, a RESTful web service and ubiquitous UI for accessing HPC resources (2016)
This paper describes the design of a user interface between a high-throughput computing pool system like HTCondor and a device-independent user interface. This design aims to bring parallel tools and resources to a novel academic community. No matters how and where are resources allocated, users can be access from own their hands with GridUI. © 2016 IEEE.